Pengaruh Segmenting, Targeting, dan Positioning terhadap Minat Pembelian di Konter Perdana Cell : (Survei pada Konsumen Konter Perdana Cell) - Endah Khoerun Nissa; Arga Sutrisna; Suci Putri Lestari (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This study aims to determine the effect of segmenting, targeting and positioning on purchase intention at the Dadaha cell prime counter. The dependent variable in this study is purchase intention (Y) while the devendent variables include segmenting (X1), targeting (X2), positioning (X3). The method used in this research is quantitative method. The population in this study were consumers of the dadaha cell prime counter in the dadaha area of tasikmalaya city. The sampling technique in this study used random sampling so that a sample of 100 respondents was obtained. The data collection technique is to use a questionnaire distribution. The results of this study indicate that: 1) segmenting variables have a positive and significant effect on buyer interest. 2) targeting variables have a positive and insignificant effect on purchase intention. 3) positioning variables have a positive and significant effect on purchase intention. From the results of the f test it can be concluded that together or simulatan segmenting, targeting and positioning variables have a positive and significant effect on purchase intention.